Basophils in acute myeloid leukaemia. Issue 8 (August 1989) - Hoyle, C F; Sherrington, P D; Fischer, P; Hayhoe, F G
Abstract : Thirty four out of 750 patients entered into the Medical Research Council's (MRC) 9th Acute Myeloid Leukaemia Trial had more than 1% basophils (range 1-27%) often with bizarre granulation and primitive forms, a rare finding in this disease. Both normal and abnormal karyotypes were present including abnormalities of 6p, 12p, and the Philadelphia chromosome. Basophilia was found in both "monolineage" and "multilineage" leukaemias and the commonest French-American-British (FAB) classification group was M2, followed by M4. Basophilia did not seem to be associated with a worse prognosis, although cases with abnormalities of 6p died of disease that was resistant to first line conventional chemotherapy.